Characterisation and application of carbon film electrodes in room temperature ionic liquid media - Pauliukaite, Rasa (2008)
Carbon film electrodes have been characterised in the room temperature ionic liquids, 1-butyl-3-methylimidazolium bis(trifluoromethane)sulfonimide (BmimNTF2), 1-butyl-1-methylpyrrolidinium bis(trifluoromethane)sulfonimide, (BpyrNTF2) and 1-butyl-3-methylimidazolium nitrate (BmimNO3), by cyclic voltammetry and electrochemical impedance spectroscopy. The electrochemical behaviour of the ionic liquids depended on both cation and anion of these electrolytes. Oxygen reduction is clearly visible at carbon film electrodes - after oxygen removal the potential window was wider, that of BpyrNTF2 being the widest. These room temperature ionic liquids were used in the electrochemical investigation of two ferrocene derivatives, benzoyl- and acetyl-ferrocene, that are both insoluble in water and cannot be investigated in aqueous solutions. They were also applied in the investigation of two sensor and biosensor mediators, copper hexacyanoferrate and poly(neutral red), with a view to using ionic liquids as electrolytes in electrochemical sensing and biosensing systems.